An Overview of the Management of the Embroidery Skills Program as an Effort to Empower Teenagers at Panti Sosial Bina Remaja Harapan Padang Panjang City - Sefa, Asya Tridu; Solfema, Solfema (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
This research is motivated by success of embroidery skills training program which was marked by the success of the embroidery training participants at the UPTD Social Institution for Youth Development in Padang Pnajang City who were absorbed in the world of work market. This is allegedly due to the management of the implementation of the training program. This study aims to describe the management of the embroidery skills program in terms of planning, evaluation and implementation. It is type research a quantitative descriptive research. The subjects of this study were embroidery training participants at the UPTD Center for Community Development in Padang Panjang City. The samples taken were 50 training participants. The collection data technique used by researchers is a questionnaire. Data collection instrument used by researchers is a questionnaire. The data analysis technique uses the percentage formula. The results of the research show that the management of embroidery skills Training Program at the UPTD Social Institution for Bina Adolescents in Padang Panjang City, from a planning perspective, was categorized as a planned program according to needs. Second, in terms of implementation, the material provided is categorized as needed. Third, in terms of evaluation, it is categorized as training participants who are able to understand the theory and practice provided well.Keywords: Program management, training institusion